Novel Nanocombinations of l-Tryptophan and l-Cysteine: Preparation, Characterization, and Their Applications for Antimicrobial and Anticancer Activities - Ahmed I. Abd-Elhamid; Hamada El-Gendi; Abdallah E. Abdallah; Esmail M. El-Fakharany (MDPI AG, 2021)
Tungsten oxide WO3 nanoparticles (NPs) were prepared in a form of nanosheets with homogeneous size and dimensions in one step through acid precipitation using a cation exchange column. The resulting WO3 nanosheet surface was decorated with one of the two amino acids (AAs) l-tryptophan (Trp) or l-cysteine (Cys) and evaluated for their dye removal, antimicrobial, and antitumor activities. A noticeable improvement in the biological activity of WO3 NPs was detected upon amino acid modification compared to the original WO3. The prepared WO3-Trp and WO3-Cys exhibited strong dye removal activity toward methylene blue and safranin dyes with complete dye removal (100%) after 6 h. WO3-Cys and WO3-Trp NPs revealed higher broad-spectrum antibacterial activity toward both Gram-negative and Gram-positive bacteria, with strong antifungal activity toward Candida albicans. Anticancer results of the modified WO3-Cys and WO3-Trp NPs against various kinds of cancer cells, including MCF-7, Caco-2, and HepG-2 cells, indicate that they have a potent effect in a dose-dependent manner with high selectivity to cancer cells and safety against normal cells. The expression levels of E2F2 and Bcl-2 genes were found to be suppressed after treatment with both WO3-Cys and WO3-Trp NPs more than 5-FU-treated cells. While expression level of the p53 gene in all tested cells was up-regulated after treatment 5-8 folds more as compared to untreated cells. The docking results confirmed the ability of both NPs to bind to the p53 gene with relevant potency in binding to other tested gens and participation of cysteine SH-functional group in such interaction.